Pennsylvania : the Keystone State - Hamilton, John, 1959- (2017)
Presents the history, geography, climate, plants and animals, cities, transportation, natural resources, industry, sports, entertainment, and people of Pennsylvania, as well as general facts about the state.
The Keystone State -- Quick facts -- Geography -- Climate and weather -- Plants and animals -- History -- Did you know? -- People -- Cities -- Transportation -- Natural resources -- Industry -- Sports -- Entertainment -- Timeline -- Glossary -- Index.
Includes index.
"Established in 1787"--Cover.
Keywords: Pennsylvania -- Juvenile literature; Pennsylvania -- History -- Juvenile literature; Pennsylvania; Pennsylvania; History; Juvenile works